Absolute accuracy analysis and improvement of a hybrid 6-DOF medical robot. Issue 1 (19th January 2015) - Joubair, Ahmed; Zhao, Long Fei; Bigras, Pascal; Bonev, Ilian
Abstract : Purpose: – The purpose of this paper is to describe a calibration method developed to improve the accuracy of a six degrees-of-freedom medical robot. The proposed calibration approach aims to enhance the robot's accuracy in a specific target workspace. A comparison of five observability indices is also done to choose the most appropriate calibration robot configurations. Design/methodology/approach: – The calibration method is based on the forward kinematic approach, which uses a nonlinear optimization model. The used experimental data are 84 end-effector positions, which are measured using a laser tracker. The calibration configurations are chosen through an observability analysis, while the validation after calibration is carried out in 336 positions within the target workspace. Findings: – Simulations allowed finding the most appropriate observability index for choosing the optimal calibration configurations. They also showed the ability of our calibration model to identify most of the considered robot's parameters, despite measurement errors. Experimental tests confirmed the simulation findings and showed that the robot's mean position error is reduced from 3.992 mm before calibration to 0.387 mm after, and the maximum error is reduced from 5.957 to 0.851 mm. Originality/value: – This paper presents a calibration method which makes it possible to accurately identify the kinematic errors for a novel medical robot. In addition, this paper presents a comparison between the five observability indices proposed in the literature. The proposed method might be applied to any industrial or medical robot similar to the robot studied in this paper.